Cyst morphology of large branchiopod crustaceans (Anostraca, Notostraca, Laevicaudata, Spinicaudata) in western Poland - Czyż, Michał Jan; Woliński, Paweł; Gołdyn, Bartłomiej (Biological Letters, 2017)
The morphology of resting eggs was studied in Polish populations of 7 large branchiopod species: Branchipus schaefferi, Chirocephalus shadini, Eubranchipus grubii (Anostraca), Lepidurus apus, Triops cancriformis (Notostraca), Lynceus brachyurus (Laevicaudata), and Cyzicus tetracerus (Spinicaudata). Scanning electron microscope photographs for each species are also provided. In some species (especially E. grubii), the ornamentation and size of cysts from Polish populations significantly differ from literature data for populations from other parts of Europe. We also present a key to determination of the studied species based on cyst morphology and discuss whether those traits are useful in surveys of new localities of endangered large branchiopods.